ANALISIS PENGARUH PENAMBAHAN LIMBAH KARET TERHADAP DURABILITAS DAN FLEXIBILITAS ASPAL BETON (AC-WC) - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
Availability of roads is an absolute prerequisite for the entry of investment into a region, for this reason it is necessary to plan strong, durable and high durability pavement for plastic deformation. Damage in Indonesia is generally caused by excessive loading. The cause of damage to this pavement requires the use of material for higher quality road pavement in the form of aggregate material as a filler and asphalt as a binder. The addition of rubber waste to the concrete asphalt mixture is a solution for highway planning and reducing pollution of rubber waste produced by rubber factories. From the results of the addition of rubber waste mixture affect the flexibility and durability of asphalt, Marshall Quotien value and residual Marshall Stability that affect flexibility and durability when compared with normal mixtures decreased, the decrease in value was due to the number of cavities in the test object mixed with rubber waste. From the results of the mixture of rubber waste produced an optimization value on Marshall stability in the percentage of 6% rubber waste of 93.68% and Marshall Quotien in the percentage of 6% rubber waste of 272.20 kg / mm.